Studies on consumptive use of water for wetland paddy in Tavanur region - ABDUL HAKKIM, V. M; Abdul Wahab V. M; Asha Joseph; Saji M. Kuriakose (Tavanur Kelappaji Collge of Agricultural Engineering and Technology, 1990)
Project report
Project report